Analysis of Money Demand in Indonesia - Muhammad Harun; Anthoni Mayes; Iva Desman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research is aimed to 1) find out and analyze the effect of national income, rate of saving interest, and inflation into money demand in Indonesia. 2) to find out and analyze the dominant factor from national income variable, rate of saving interest, and inflation into money demand in Indonesia.This research was done in indonesia, focused on Bank of Indonesia as an institution which have responsible for releasing and controlling rupiahs money.Data used ini this research is secondary data, got from some relating institutions; Bank of Indonesia branc Pekanbaru, and Badan Pusat Statistic (Statistic Bureau) Riau Province. Data analysis was done using descriptive analysis method, started by collecting, tabulate,process, and analyze the data for summary.Result shows that national income per capita have significant effect to money demand in Indonesia.As an opposite, rate of saving interest and inflation have no signifficant effect. So, the most dominant variable to money demand in Indonesia is national income per capita.Key word: national income, rate of deposito interest, inflation, money demand